Multiplex PCR for the detection of putative virulence factor genes mviN and vacB in Pasteurella multocida B: 2 strains - CHACHRA, DEEPTI; PARTON, ROGER; COOTE, JOHN G; JAND, S K (The Indian Journal of Animal Sciences, 2013)
Vacuolating cytotoxic activity in the mouse macrophage cell line RAW 264 was reported in Pasteurella multocida B: 2 strains associated with haemorrhagic septicaemia in buffaloes and cattle. A putative virulence-related gene mviNwas reported in the sequenced genome of P. multocida serotype A (avian strain Pm70). MviN is an integral membraneprotein that belongs to MATE (multi-antimicrobial extrusion) family. The present study was undertaken to detect thepresence of putative virulence- related genes, viz. vacB and mviN among P. multocida B: 2 strains (8). Sequenceinformation for the vacB gene was obtained from the sequenced genome of P. multocida serotype A (avian strainPm70). Oligonucleotide primers were designed for these genes and synthesized. All the 8 P. multocida B: 2 strains, 1 P.multocida type A 3 (bovine) and 1 P. multocida type D (pig) strain had both of these genes of the expected size (1.5 Kbfor mviN and 2.4 Kb for vacB) as confirmed by PCR. E. coli K12 used as negative control did not show any band. Boththese putative virulence-related genes were amplified in a single reaction mixture using multiplex PCR. The expectedsize (1.5 Kb for mviN and 2.4 Kb for vacB) of both the genes was obtained. This is the first report of the detection ofthese virulence-related genes among P. multocida B: 2 strains. Besides providing additional targets for diagnosticapplications, the identification and subsequent analysis of virulence-related genes in P. multocida B: 2 strains may helpin improving our understanding of molecular mechanism of adaptation, survival and virulence of P. multocida B: 2